2022
DOI: 10.3390/md20050292
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polyether Ionophores and Their Pharmacological Profile

Abstract: This review is devoted to the study of the biological activity of polyether ionophores produced by bacteria, unicellular marine algae, red seaweeds, marine sponges, and coelenterates. Biological activities have been studied experimentally in various laboratories, as well as data obtained using QSAR (Quantitative Structure–Activity Relationships) algorithms. According to the data obtained, it was shown that polyether toxins exhibit strong antibacterial, antimicrobial, antifungal, antitumor, and other activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 238 publications
(267 reference statements)
0
7
0
Order By: Relevance
“…Notably, the well-known Na + ionophores, such as monensin A, lasalocid, and salinomycin, have been extensively utilized in veterinary practice for controlling coccidiosis. Their effectiveness in this application is closely tied to their capacity to bind and transport Na + across cell membranes [ 45 ]. Monensin A, a representative polyether ionophore, is an intermediate biosynthetic metabolite produced by Streptomyces cinnamonensis bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the well-known Na + ionophores, such as monensin A, lasalocid, and salinomycin, have been extensively utilized in veterinary practice for controlling coccidiosis. Their effectiveness in this application is closely tied to their capacity to bind and transport Na + across cell membranes [ 45 ]. Monensin A, a representative polyether ionophore, is an intermediate biosynthetic metabolite produced by Streptomyces cinnamonensis bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Polyether antibiotics are a class of ionophoric polyketides with a variety of biological properties including antibacterial 240 and cytotoxic, 240,241 as well as antiparasitic activity that has seen them used in veterinary medicine as ruminant non-hormonal growth promoters, and as coccidiostatic agents in livestock and poultry breeding. 242 In a recent 2022 account, nigericin ( 4.114 ) was reported as the anthelmintic principle of Streptomyces sp.…”
Section: Bacteriamentioning
confidence: 99%
“…Several comparative studies have shown that PASS is more predictive than some other recently developed methods for assessing biological activity profiles [197,198], although this program is not sufficiently effective for complex molecules or optical isomers. To calculate the pharmacological potential profile of natural substances, we have successfully used PASS for the past fifteen years [200][201][202][203][204][205].…”
Section: Structure-activity Relationships and Biological Activities O...mentioning
confidence: 99%